2015
DOI: 10.1039/c5tc01224d
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent structural, elastic, and polar properties of ferroelectric polyvinylidene fluoride (PVDF) and trifluoroethylene (TrFE) copolymers

Abstract: We use molecular dynamics to calculate the structural, elastic, and polar properties of crystalline ferroelectric β -poly(vinylidene fluoride), PVDF (-CH 2 -CF 2 -) n with randomized trifluoroethylene TrFE (-CHF-CF 2 -) n as a function of TrFE content (0-50%) in the temperature range of 0-400 K. There is a very good agreement between the experimentally obtained and the computed values of the lattice parameters, thermal expansion coefficients, elastic constants, polarization, and pyroelectric coefficients. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 62 publications
(156 reference statements)
0
36
0
Order By: Relevance
“…In most of the current models the role of chain tacticity has been, unfortunately, overlooked. For instance, most studies focus on quantifying or reproducing the ferroelectric properties of PVDF and P(VDF‐TrFE)s with the assumption that the all‐ trans conformation is the ground state of the polymers . A more recent density functional theory study ignored the contributions of chain tacticity and showed that all‐ trans conformation is the most energetically favorable for both P(VDF‐TrFE)s and PTrFE, which is in contrast to recent experimental results on P(VDF‐TrFE)s and PTrFE as well as the previous conformational energy calculations on PTrFE .…”
Section: Origin and Tuning Of Negative Longitudinal Piezoelectric Coementioning
confidence: 75%
See 1 more Smart Citation
“…In most of the current models the role of chain tacticity has been, unfortunately, overlooked. For instance, most studies focus on quantifying or reproducing the ferroelectric properties of PVDF and P(VDF‐TrFE)s with the assumption that the all‐ trans conformation is the ground state of the polymers . A more recent density functional theory study ignored the contributions of chain tacticity and showed that all‐ trans conformation is the most energetically favorable for both P(VDF‐TrFE)s and PTrFE, which is in contrast to recent experimental results on P(VDF‐TrFE)s and PTrFE as well as the previous conformational energy calculations on PTrFE .…”
Section: Origin and Tuning Of Negative Longitudinal Piezoelectric Coementioning
confidence: 75%
“…Consequently, the regioregularity was not properly described while the chain tacticity was not analyzed. This is also one of main reasons why theoretical works considered only VDF‐TrFE as the model of P(VDF‐TrFE) copolymers . The regiosequences were explicitly determined based on the assignments of 19 F NMR signals of P(VDF‐TrFE) copolymers ( Table 2 ).…”
Section: Origin and Tuning Of Negative Longitudinal Piezoelectric Coementioning
confidence: 99%
“…PVDF-TrFE forms the β-phase through copolymerization without the need for mechanical stretching or drawing [208]. In the case of additional annealing, mechanical stretching, or electrical poling, it is possible to further increase the crystallinity and alignment of the CF2 dipoles, thereby inducing higher piezoelectricity as compared to homopolymer PVDF, dependent on the TrFE content [209]. Electrospun PVDF-TrFE fibrous scaffolds showed higher crystallinity and β-phase content as compared to the starting powder material for neural and bone tissue engineering [101][102][103][104].…”
Section: Poly-vinylidene Fluoride-trifluoroethylenementioning
confidence: 99%
“…To model the inter-and intra-molecular interactions, we use the MSXX force field, 40 which is widely used for studying PVDF-related molecules. [41][42][43][44][45][46][47] The version without the shell model is used because the shell parameters for the TrFE and CFE monomers are not available. While density functional theory (DFT) calculations are more accurate than those from force fields, they are limited by large computational demands.…”
Section: A Msxx Force Fieldmentioning
confidence: 99%